The limitations of the legal framework in addressing the problem of child labour in artisanal and small-scale mining in Zimbabwe - Mutendera, Chiyedza Ennah (Centre for Law and Society, 2026)
Whilst the rights of children are protected in various legal instruments both at domestic and international level, reality stands in stark contrast to the aspirations for children expressed in these legal instruments. The socio-economic conditions people in developing countries, particularly those in poor rural areas of developing countries like Zimbabwe has pushed people into artisanal and small-scale mining (ASM) of various minerals for survival. Many children in these families and those of child-headed homes also participate in ASM to the extent of dropping out from school. The ASM environment, which is largely informal thus lacking government oversight, using rudimentary methods to extract minerals and hosting criminals and violent gangs, is not conducive for children and in many ways violates children`s rights. Children are involved in hazardous and hard work in violation of international standards governing child labour. Children are exposed to toxic chemicals harmful to their physical development and to prostitution, drug abuse, sexual abuse, and human trafficking in ASM. This research, through a doctrinal research methodology, examined the problem of child labour and recommended that the government formalize ASM in Zimbabwe to enhance oversight on conditions of work, restrict child participation, and ensure that participants in ASM develop skills and derive value for their mineral output. The formalized ASM industry must specifically accommodate women and mature children to earn a living. Further, the government must expand funding for primary and secondary school education and social security for families to eliminate the urgency drawing children into ASM.